Advanced electrochemical energy storage and conversion on graphdiyne interface - Gao, Xiaoya (2024)
The research in graphdiyne (GDY) has experienced a rapid growth period in the first decade after its birth. As a new two-dimensional (2D) atomic crystal, GDY has unique structures consisting of both sp and sp2 hybridized carbon atoms, and exhibits many unprecedented intrinsic properties to scientists. Due to the inherent characteristics of GDY, some new phenomena and properties have been discovered in a wide range of research fields. GDY has made substantial breakthroughs in fundamental and applied science, formed innovative scientific concepts, and made great achievements. In these fields, the electrochemical energy storage and conversion are two important and impressive fields for the fundamental applicative investigations. This review focuses on the utilization of GDY as advanced electrochemical interface for the electrochemical energy storage and conversion. It begins with an introduction of the superiorities and inherent compatibilities of GDY as the electrochemical interface. Then, GDY's recent achievements in electrochemical storage and conversion are commented, from which we can appreciate the inherent advantages of GDY as a crucial material for alternating and innovating the electrochemical interface. Finally, new insights into the challenges and further perspectives on the GDY interface for the electrochemical energy storage and conversion are discussed, aiming at prompting in-depth investigation and their performance in practical applications.